Strategi pengelolaan kawasan Pantai Panjang sebagai wisata bahari di kota Bengkulu - Febriyanti Febriyanti; Mubarak Mubarak; Hendrik Hendrik (Jurnal Zona, 2020)
The coastal area of Bengkulu City's Long Beach currently has natural, cultural and historical tourism and forest tourism. However, tourism in Bengkulu City's Long Beach is still not optimal in its management. In addition to increasing the diversity of tourism in the Long Beach area of the city of Bengkulu, alternative tourism is needed, namely marine tourism in the city of Bengkulu. To support the management of Bengkulu City Long Beach tourism area as a marine tourism area, it is necessary to manage and develop Bengkulu City Long Beach area in accordance with the conditions and pay attention to the potential of natural resources around the area.This study aims to examine and analyze how the strategy of managing the Long Beach area of Bengkulu city becomes an integrated and sustainable marine tourism area.